Influence of high temperature interaction between iron ores on the formation behavior of primary slags - WU Sheng-li; WANG Lai-xin; WANG Yu-jue; ZHANG Jia-cong (工程科学学报)
To explore the effect of high temperature interaction between sinter and lump ores on the formation behaviors and characteristics of primary slags, experimental and theoretical methods were used to study the primary-slag formation behaviors and characteristics of sinter, lump ores and their integrated burdens in a blast furnace. The results show that the primary-slag formation temperature intervals of single iron ores are wide. Due to the high temperature interaction the primary-slag formation behavior markedly improves and the viscosity of primary slags decreases. However, the high temperature interaction is influenced by the chemical composition, reducing properties and porosity of iron ores.